Validity of the Autism Mental Status Exam in Developmental Pediatrics and Primary Care Settings. (May 2019) - Betz, Eugenia; Hackman, Nicole M.; Mayes, Susan; Chin, Eric M.; Ivy, Jonathan W.; Tierney, Cheryl
The Autism Mental Status Exam (AMSE) is a brief clinician-completed observational instrument that has shown promise in identifying autism spectrum disorder (ASD) in a referred sample. Our study explores the feasibility of the AMSE in both developmental pediatric and primary care samples. Fifty-three toddlers with ASD and other disabilities were scored using the AMSE and compared with 55 typically developing toddlers. AMSE scores differed significantly between ASD, non-ASD developmental disability, and neurotypical groups. A cutoff score on the AMSE of ≥5 for ASD maximized sensitivity (81.2%) and specificity (90.5%). Score differences between groups suggest that the AMSE may be useful in a clinical setting to help identify children with possible ASD.